Sanitary protection of the territory of Russian Federation. Report 2. The differentiation of the territory of a region of Russian Federation for risk of diseases dangerous for people - A. K. Noskov (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The risk of emergency situations in the sphere of sanitary-epidemiological welfare associated with diseases dangerous for population varies for different municipalities of a region of Russian Federation. Therefore a differentiation of a region for three types of territories (A, B, C) is necessary. Adequate number of sanitary protection measures is determined for each type of territories. The purpose of this study was the development of methodical reception for differentiation of a region of Russian Federation. Point scoping of criteria of external and. internal epidemiological risks for each of municipality is proposed as this method. Criteria of external epidemiological risk allow to take into account the probability of the importation of infectious diseases, requiring measures for sanitary protection of the territory. Criteria of internal epidemiological risk reflect both actual and. potential dangers: morbidity, the registration of particular nosologic forms of diseases in animals and. detection of pathogens in the living and. non-living environment objects. Assessment of internal risk is carried out in the analysis of information about epizootic and. epidemiological situation of infectious diseases, the list of which is proposed, with, consideration of their epidemiological significance and. can be used for any Russian Federation region. According to the results of total assessment of risks for each of municipalities the complex index of epidemiological risk (CIER) is determined. On the basis of CIER the territory type (A, B, C) is determined. Type A, B or C defines for the municipality the volume of measures for sanitary protection of the territory on the basis of a sufficient level for preparedness of forces and means of public health institutions. The method, based, on the assessment of external and. internal epidemiological risks, that allows to differentiate the region of Russian Federation, at municipal level for risk of diseases dangerous for people, is proposed, as the result of this work. A new methodical approach, will contribute to the increase of the preparedness of public health, institutions to emergency situations in the sphere of sanitary-epidemiological welfare associated, with, diseases dangerous for people.